2017
DOI: 10.1080/10942912.2017.1315130
|View full text |Cite
|
Sign up to set email alerts
|

A review on the status of the phenolic compounds and antioxidant capacity of the flour: Effects of cereal processing

Abstract: Cereals are important grains that are largely used for food and source of bioactive compounds such as starch, dietary fibre, amino acids, minerals, vitamins, and phenolic compounds. However, the use of cereals in the food industry subjects these cereals to different processes that can alter the phenolic content and cause degradation of their antioxidant properties. Understanding the influence of processing operations such as germination, fermentation, and thermal processing on the phytochemicals of cereals gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Enzymes such as amylases and proteases produced by starter culture could hydrolyze phenolic conjugates with one or more bounded sugar into free polyphenols (Shrestha, Dahal, & Ndungutse, 2013). Kadiri (2017) reported that Saccharomyces cerevisiae could synthesize some enzymes, including β‐glucosidase, cellulase, and xylanase, which have the capability to hydrolyze the β‐glycosidic bonds of certain polyphenols. Therefore, the significant decrease in TFC and CTC but limited change of TPC was the result of the combined effects of enzymatic, physical, and biochemical activities during the fermenting process.…”
Section: Resultsmentioning
confidence: 99%
“…Enzymes such as amylases and proteases produced by starter culture could hydrolyze phenolic conjugates with one or more bounded sugar into free polyphenols (Shrestha, Dahal, & Ndungutse, 2013). Kadiri (2017) reported that Saccharomyces cerevisiae could synthesize some enzymes, including β‐glucosidase, cellulase, and xylanase, which have the capability to hydrolyze the β‐glycosidic bonds of certain polyphenols. Therefore, the significant decrease in TFC and CTC but limited change of TPC was the result of the combined effects of enzymatic, physical, and biochemical activities during the fermenting process.…”
Section: Resultsmentioning
confidence: 99%
“…For the experiment, it was necessary to autoclave oat grains before the treatments, hence, the initial content in each variety was not known because thermal processing can lead to a degradation of flavonoids (Buchner et al 2006). Both, decreasing and increasing effects, were observed for phenolic acids as recently reviewed by Kadiri (2017). Nevertheless, it is likely that the fungus metabolised an extensive amount of the endogenous phenolic compounds leading to the observed differences between the control and the inoculated treatment, which was also reported by Bilska et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…Processing techniques may affect the phenolic content and antioxidant properties of vegetables, fruits, whole grains, and legumes (Adefegha & Oboh, ; Oboh, Ademosun, Olasehinde, Oyeleye, & Ehiakhamen, ). Although some processing techniques such as cooking, boiling, and roasting have been reported to reduce the phenolic content and antioxidant properties of some foods (Kadiri, ; Lemos, Siqueira, Arruda, & Zambiazi, ), these same processing methods have been reported to increase the phenolic content, antioxidant, and antidiabetic properties of other foods (Sharma & Gujral, ; Oboh, Ademosun, et al., ). Pasting is a traditional processing method that is common in West Africa.…”
Section: Introductionmentioning
confidence: 99%